Characteristic comparison of lignocellulose nanofibrils from wheat straw having different mechanical pretreatments. Issue 43 (24th August 2022) - Yan, Ming; Wu, Ting; Ma, Jinxia; Lu, Hailong; Zhou, Xiaofan
Abstract: Wheat straw (WS) was considered the most abundant agricultural residue in China. Therefore, it was meaningful to explore the effective utilization of WS. Thus far, WS has been considered a potential raw material to produce lignocellulose nanofibrils (LCNFs) with the rapid development of nanotechnology. Unfortunately, the existing methods of LCNFs preparation directly from WS still faced some hurdles. Herein, screw extrusion and ball milling considered the common mechanical pretreatments were employed to directly prepare LCNFs from WS. The different impacts of screw extrusion and ball milling pretreatments on the properties of LCNFs were revealed by systematically comparing physicochemical analyses. The results showed that the crystalline and chemical structure of samples was little affected by the mechanical pretreatment. However, the mechanical pretreatment caused a change in the morphology, yield, and chemical composition of LCNFs. LCNFs prepared by screw extrusion with a high yield of 73% had the narrowest diameter distribution (0 ~ 80 nm), the most cellulose content (51.1%), and the maximum crystallinity degree (44.7%). LCNF samples all exhibited good thermal stability. This work could not only offer theoretical guidance on the preparation of LCNFs by mechanical pretreatments but also expand the high‐value application of WS in polymer composites. Abstract : Herein, the morphology, physicochemical structure, chemical composition, and thermostability of Wheat straw (WS) and lignocellulose nanofibrils (LCNFs) were systematically investigated, aiming to reveal the impact of screw extrusion and ball milling during the process of LCNF preparation. This work could not only offer theoretical guidance on the preparation of LCNFs by mechanical pretreatments but also expand the high‐value application of agricultural residues in polymer composites.